PENGARUH PROFESIONALISME, KOMITMEN ORGANISASI, IKLIM ORGANISASI, STRES KERJA DAN INSENTIF TERHADAP KINERJA ACCOUNT REPRESENTATIVE PADA KANTOR PELAYANAN PAJAK DI PROVINSI RIAU - Wenny Risanti; Novita Indrawati; Rofika ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study is to examine the influence of professionalism, organizational commitment, organizational climate, job stress and incentive to account representative performance at the tax service office in Riau. The population in this study are all account representatives that working at 8 the tax service office in Riau. The samples used with saturated sampling method or census. The data used are primary data collected through questionnaires. Questionnaires which can be processed a total of 110 questionnaires from 137 questionnaires distributed. The data were analyzed using multiple regression analysis and assisted with SPSS version 21. The variables were examined are the influence of professionalism, organizational commitment, organizational climate, job stress and incentive to account representative performance. The results of this study indicate that the professionalism, organizational commitment, job stress and incentive influence on the account representative performance. While the organizational climate has not influence the account representative performance. Overall, the professionalism, organizational commitment, organizational climate, job stress and the incentive influence on the account representative performance by 59.2%. While 40.8% are influenced by other variables that did not examined on this research.Keywords : Professionalism, Commitment, Climat, and Account Representative